Characteristics of Customer Who Makes Allocation for Pension Plan in Indonesia - Hendra Achmadi; Isana Sri Christina Meranga; Sylvia Samuel (Universitas Pelita Harapan, 2025)
This study sought to determine which characteristic from Indonesian people are most likely to make allocation for pension, and how to identify the key factors driving these purchases pension products. Recognizing Indonesia's relatively low allocation in pension plan, researchers analyzed a targeted sample of 199 data points from 38 companies across various sectors. Using the CRISP-DM data mining methodology, to determine what characteristics from customer with over 20 % allocation into the pension product, and in this study found that marriage status, income, industry, education, sex, domicile, electricity, position, age, status of property. The CRISP-DM process, which included defining objectives, data collection, preparation, modeling, and property ownership, as a characteristic of customer to invest in pension. This research uses data mining methodology with resulted in a model with 73.33 % accuracy. 1 The analysis revealed that the result demonstrated the highest stock market allocation by customers is based on industry (0,2), Listrik (0,13), Makan (0,12), transport (0,11), Pendidikan (0,10), income (0,06).